2007
DOI: 10.3748/wjg.v13.i38.5127
|View full text |Cite
|
Sign up to set email alerts
|

N-acetylcysteine attenuates oxidative stress and liver pathology in rats with non-alcoholic steatohepatitis

Abstract: AIM:To evaluate attenuating properties of N-acetylcysteine (NAC) on oxidative stress and liver pathology in rats with non-alcoholic steatohepatitis (NASH). METHODS:Male Sprague-Dawley rats were randomly divided into three groups. Group 1 (control, n = 8) was free accessed to regular dry rat chow (RC) for 6 wk.Group 2 (NASH, n = 8) was fed with 100% fat diet for 6 wk. Group 3 (NASH + NAC20, n = 9) was fed with 100% fat diet plus 20 mg/kg per day of NAC orally for 6 wk. All rats were sacrificed to collect blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
45
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(50 citation statements)
references
References 24 publications
4
45
1
Order By: Relevance
“…These compounds can counteract hepatocyte injury associated with lipid peroxidation and chronic oxidative stress. Some authors have reported a positive effect of dietary antioxidants such as vitamins C and E [5,6], bioactive compounds like resveratrol [7] and lycopene [8,9], and antioxidant drugs such as N-acetylcysteine [10] on the biomarkers of NAFLD, as well as highlighting that they impede progression toward NASH in both human and animal models. Tomatoes are characterized by a low fat and protein content, and are rich in phenolic compounds, carotenoids, and vitamins C and E [11,12].…”
Section: Introductionmentioning
confidence: 98%
“…These compounds can counteract hepatocyte injury associated with lipid peroxidation and chronic oxidative stress. Some authors have reported a positive effect of dietary antioxidants such as vitamins C and E [5,6], bioactive compounds like resveratrol [7] and lycopene [8,9], and antioxidant drugs such as N-acetylcysteine [10] on the biomarkers of NAFLD, as well as highlighting that they impede progression toward NASH in both human and animal models. Tomatoes are characterized by a low fat and protein content, and are rich in phenolic compounds, carotenoids, and vitamins C and E [11,12].…”
Section: Introductionmentioning
confidence: 98%
“…The synthesis of GSH is limited by the availability of cysteine [18]. Clinically, NAC is used as a mucolytic agent in patients with cystic fibrosis [19], as an antidote in the treatment of acetaminophen overdose [20] and also used in the prevention of non-alcoholic steatohepatitis (NASH), characterized by decreased GSH and increased oxidative stress [21]. NAC is considered a better source of glutathione than glutathione itself, due to the low oral absorption of the latter.…”
Section: Introductionmentioning
confidence: 99%
“…In the bile duct occlusion rat model, the oxidative damage was activated, and the lack of antioxidant capacity increased the liver fibrosis score and the degree of fibrosis. Thymoquinone can significantly reduce oxidative damage, improve the antioxidative effect on the liver, and reduce the fibrosis score (Birkner et al, 2007;Thong-Ngam et al, 2007;Singer et al, 2011). Therefore, we hypothesized that the protective effect of thymoquinone on liver injury was associated with the reduction of hepatic oxidative stress byproduct levels and improvement of the endogenous antioxidant system (Badary et al, 1998;Mansour et al, 2002).…”
Section: Discussionmentioning
confidence: 99%